2009
DOI: 10.1073/pnas.0912048107
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids selectively enhance sweet taste

Abstract: Endocannabinoids such as anandamide [N-arachidonoylethanolamine (AEA)] and 2-arachidonoyl glycerol (2-AG) are known orexigenic mediators that act via CB 1 receptors in hypothalamus and limbic forebrain to induce appetite and stimulate food intake. Circulating endocannabinoid levels inversely correlate with plasma levels of leptin, an anorexigenic mediator that reduces food intake by acting on hypothalamic receptors. Recently, taste has been found to be a peripheral target of leptin. Leptin selectively suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 40 publications
5
166
1
4
Order By: Relevance
“…Hormones that bind to receptors on taste cells alter the palatability of food and, therefore, intake. Current knowledge of the hormonal modulation of taste function is summarized in Table 1 [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] and described in greater detail below.…”
Section: Hormonal Modulation Of Taste Functionmentioning
confidence: 99%
“…Hormones that bind to receptors on taste cells alter the palatability of food and, therefore, intake. Current knowledge of the hormonal modulation of taste function is summarized in Table 1 [60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] and described in greater detail below.…”
Section: Hormonal Modulation Of Taste Functionmentioning
confidence: 99%
“…Blockage of cannabinoid CB 1 receptors diminishes and delays responses to food odorants (Czesnik et al, 2007). Furthermore, CB 1 receptors in type II taste cells have been shown recently to participate in the enhancement of sweet taste (Yoshida et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently revealed that endocannabinoids enhance sweet taste sensitivity via CB1 in peripheral T1r3 expressing sweet taste cells (Yoshida et al, 2010). Moreover, AT1 and CB1 form receptor heteromers, resulting in the potentiation of AT1 signaling in hepatic stellate cells from ethanol-administered rats (Rozenfeld et al, 2011).…”
Section: Enhancing Effect Of Angii On Sweet Taste Sensitivity Is Medimentioning
confidence: 99%